1996
DOI: 10.1017/s0007485300052317
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive significance of changes in morph production during the transition from parthenogenetic to sexual reproduction in the aphid Rhopalosiphum padi (Homoptera: Aphididae)

Abstract: Many aphid species have life cycles which alternate between asexual reproduction during spring and summer and sexual reproduction in autumn. This paper describes the sequences of morphs produced by clones of Rhopalosiphum padi (Linnaeus) in response to a range of photoperiods and temperatures in the laboratory, and under semi-natural conditions at the time of year when the transition from parthenogenetic to sexual reproduction occurs. By using similarities in the order in which the various morphs were born, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Fecundity was also similar and only the percentage of sexual morphs differed, with less sexual morphs produced in outdoor compared to laboratory conditions. Austin et al (1996) also observed that in field conditions, the date of sexual production (mainly for the males) for different genotypes of Rhopalosiphum padi was different compared to controlled conditions. Beside the essential role of photoperiod in triggering the switch of reproductive mode in aphids, these studies indicate that climatic features interact with the photoperiod to modify the proportion and time of release of sexual morphs in autumn (Lees, 1959).…”
Section: Introductionmentioning
confidence: 81%
“…Fecundity was also similar and only the percentage of sexual morphs differed, with less sexual morphs produced in outdoor compared to laboratory conditions. Austin et al (1996) also observed that in field conditions, the date of sexual production (mainly for the males) for different genotypes of Rhopalosiphum padi was different compared to controlled conditions. Beside the essential role of photoperiod in triggering the switch of reproductive mode in aphids, these studies indicate that climatic features interact with the photoperiod to modify the proportion and time of release of sexual morphs in autumn (Lees, 1959).…”
Section: Introductionmentioning
confidence: 81%
“… Allochronic isolation . Heterozygote deficit could also result from a Wahlund effect within sexual populations due to differences in the timing of production of sexuals between aphid lineages (Austin et al . 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In general, a parthenogenetic mother will first produce parthenogenetic and/or sexual females and later produce males (and, under some conditions, a series of parthenogenetic females continues until death): see e.g., Acyrthosiphon pisum (Lamb & Pointing, 1972, 1975MacKay et al, 1983;Erlykova, 2003), Acyrthosiphon svalbardicum (Strathdee et al, 1993), Aphis fabae (Tsitsipis & Mittler, 1977), Aphis gossypii (Takada, 1988), Cryptomyzus spp. (Guldemond & Tigges, 1992), Megoura viciae (Lees, 1959(Lees, , 1960, Myzus persicae (Blackman, 1972;Hales et al, 1989), Rhopalosiphum padi (Dixon & Glen, 1971;Austin et al, 1996), and Sitobion avenae (Watt, 1984;Hand & Wratten, 1985;Newton & Dixon, 1987).…”
Section: Discussionmentioning
confidence: 99%